Medical students’ perceptions of their educational environment in an integrated curriculum in Saudi Arabia - Tahani Altamimi; Johnson Alex; Sara Mattout; Noha Mitwally; Sami Alnassar (Journal of the Pakistan Medical Association, 2020)
Abstract Objective: Measure medical students’ perceptions of their educational environment (EE) and determine the potential differences in those perceptions in regard to gender and academic year of study. Methods: A cross-sectional survey was conducted with medical students enrolled at private College of Medicine in Dar Al Uloom University (DAU), Saudi Arabia during 2018-2019. The Dundee Ready Educational Environment Measure (DREEM) English version was completed by 191 of the 262 (73% response rate) students. Total, domain, and item DREEM scores were analysed using descriptive statistics, the t-test, and ANOVA. The ethical approval for the study and participants’ consent were taken. Results: Participants’ total mean DREEM score (122.49/200) was higher than that of most medical schools in Saudi Arabia. There were gender-related differences for DREEM domains. Perceptions of the EE trended higher for male students and advanced-level students. Conclusion: This study was needed in order to determine the current EE among medical students at a new private sector college with an integrated system-oriented hybrid curriculum. The overall study results illustrate a healthy EE. Areas for improvement are also noted. Keywords: Educational environment; Medical Student; Integrated curriculum; Dundee Ready Educational Environment Measure (DREEM)